Sea level trends along the South African coast from 1993 to 2022 using XTRACK altimetry, tide gauges, and GNSS measurements - Ghomsi, Franck Eitel Kemgang; Erkoc, Muharrem Hilmi; Raj, Roshin P.; Pirti, Atinc; Bonaduce, Antonio; Abiodun, Babatunde J.; Stroeve, Julienne (NATURE PORTFOLIO, 2025)
This study presents a comprehensive investigation of the complex dynamics of sea-level rise (SLR) and its multiple impacts on coastal regions in southern Africa. We meticulously analyse trends and patterns in SLR and subsidence rates using a wealth of data from 1993 to 2022, including observations from a network of 10 reliable tide gauges and XTRACK data processed using the Coastal Altimetry Approach to minimise the shortcomings of conventional coastal altimetry data. Our results show that sea level rise in coastal areas of South Africa, such as Cape Town (6.3 mm/yr), is almost double the global average (3.3 mm/yr). This alarming rate of SLR, coupled with a subsidence rate of more than 2.2 mm/yr, poses a significant and immediate threat to coastal communities, infrastructure and ecosystems. Our research also highlights the impact of seismic activity on coastal dynamics, further exacerbating the challenges posed by SLR. By incorporating the influence of earthquakes on subsidence, we provide a more nuanced understanding of the complex interplay of natural and anthropogenic factors contributing to SLR in the region. In addition, our research sheds light on the wider implications of SLR for some of Africa's most iconic and culturally significant heritage sites, highlighting the urgent need for proactive coastal management and adaptation strategies.
Keywords: Sea level rise; Subsidence rates; Southern Africa; Tide gauges; Coastal altimetry; SATELLITE ALTIMETRY; VARIABILITY; OCEAN; RETRACKER; SYSTEM; RISE; EAST; ALES; Science & Technology - Other Topics